-147=3k-3(8k+7)

Simple and best practice solution for -147=3k-3(8k+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -147=3k-3(8k+7) equation:


Simplifying
-147 = 3k + -3(8k + 7)

Reorder the terms:
-147 = 3k + -3(7 + 8k)
-147 = 3k + (7 * -3 + 8k * -3)
-147 = 3k + (-21 + -24k)

Reorder the terms:
-147 = -21 + 3k + -24k

Combine like terms: 3k + -24k = -21k
-147 = -21 + -21k

Solving
-147 = -21 + -21k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '21k' to each side of the equation.
-147 + 21k = -21 + -21k + 21k

Combine like terms: -21k + 21k = 0
-147 + 21k = -21 + 0
-147 + 21k = -21

Add '147' to each side of the equation.
-147 + 147 + 21k = -21 + 147

Combine like terms: -147 + 147 = 0
0 + 21k = -21 + 147
21k = -21 + 147

Combine like terms: -21 + 147 = 126
21k = 126

Divide each side by '21'.
k = 6

Simplifying
k = 6

See similar equations:

| -1(x+3)-3=-6(x+8) | | 5(x/5)-3(5)=5(x/5) | | 10=-7-3x | | -6z-9(-8z-4)=2-5(-9-z) | | 5(1-2x)+8=15 | | 6(x-3)-2(x-2)=1 | | 23=33-2(4-2w) | | 12/11•5/8 | | 12/8•5/8 | | 7(3x-2)=-39 | | -9x+3=-8x | | 9x+8=-1x-13 | | 3+.20y=2x+4 | | (n+18)+2n=90 | | -23=2x+3x+2 | | x/3-3=-2 | | 6(x/6)-6(4)=6(x/6) | | -17x+18=13 | | x-7=1-9 | | -7=5-2n+6n | | a+(a-15)=55 | | -8-n=0 | | 8p+3=3p+13 | | 5n+3=14-5n | | -2x+5-5x=5 | | 68mi/h=mi/sec | | (-14xy^2)/(21y^3)= | | 8x-(3x-11)=36 | | 4y=2x+9solve | | 3b^2+7b-6= | | 0.4x-8=9-0.6x | | -5=6x-4x+1 |

Equations solver categories